2007
DOI: 10.2337/db07-0551
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 Is an Endogenous Activator of TGF-β in Experimental Diabetic Nephropathy In Vivo

Abstract: OBJECTIVE—Transforming growth factor-β (TGF-β), the central cytokine responsible for the development of diabetic nephropathy, is usually secreted as a latent procytokine complex that has to be activated before it can bind to its receptors. Recent studies by our group demonstrated that thrombospondin-1 (TSP-1) is the major activator of latent TGF-β in experimental glomerulonephritis in the rat, but its role in diabetic nephropathy in vivo is unknown. RESEARCH DESIGN AND METHODS—Type 1 diabetes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 38 publications
5
83
0
3
Order By: Relevance
“…8,9 The increase in nephrin expression in LSKL-treated Akita kidneys suggests that one mechanism by which LSKL reduces proteinuria is by preventing TGF-␤-mediated podocyte damage. This would be consistent with the observations of Daniel et al, 36 who showed that diabetic TSP1 knockout mice have increased staining for the podocyte antigen desmin. LSKL treatment of rats with mesangioproliferative glomerulonephritis also preserved podocyte marker expression as measured by Wilms Tumor suppressor gene staining.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…8,9 The increase in nephrin expression in LSKL-treated Akita kidneys suggests that one mechanism by which LSKL reduces proteinuria is by preventing TGF-␤-mediated podocyte damage. This would be consistent with the observations of Daniel et al, 36 who showed that diabetic TSP1 knockout mice have increased staining for the podocyte antigen desmin. LSKL treatment of rats with mesangioproliferative glomerulonephritis also preserved podocyte marker expression as measured by Wilms Tumor suppressor gene staining.…”
Section: Discussionsupporting
confidence: 93%
“…7,30,35,36,38,39,53,54 In the present studies, we addressed whether selective targeting of only TGF-␤ activated by TSP1 would be an effective approach to reduce renal dysfunction in a mouse model of type 1 diabetes. These studies showed that i.p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…L'injection intrarénale d'oligonucléotides antisens anti-TSP-1 permet une réduction de l'activation glomérulaire du TGF- et de l'accumulation de protéines de la MEC (collagènes I et IV, fibronectine) dans un modèle de glomérulonéphrite membrano-proliférative induite par des anticorps antiThy1 chez le rat [43]. Après induction d'un diabète par la streptozocine chez les souris TSP-1 KO, l'expression glomérulaire de TGF-, des Smad2 et -3 phosphorylées et de PAI-1 (plasminogen activator inhibitor-1), l'accumulation mésangiale de fibronectine et de collagène IV, les lésions podocytaires, l'infiltration interstitielle par les macrophages et les lymphocytes, et la protéinurie sont réduites [44]. Enfin, l'activation rénale du TGF- et les lésions tubulo-interstitielles induites par l'obstruction urété-rale unilatérale sont atténuées chez la souris TSP-1 KO [29].…”
Section: Expression De La Thrombospondine-1 Au Cours Des Néphropathieunclassified